2018
DOI: 10.18203/2320-1770.ijrcog20182356
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between active and expectant management of premature rupture of membranes at term on fetomaternal and perinatal outcome in rural population

Abstract: INTRODUCTIONPremature rupture of membranes at term (PROM) is defined as a spontaneous rupture of membranes after 37 completed weeks of gestation and before the onset of regular painful uterine contractions.1 PROM occurs in 5-10% of all pregnancies of which approximately 80% occur at term. 2 The aetiology of PROM is multifactorial. 2At term, PROM can be physiological variation rather than a pathological event. PROM occurs when intrauterine pressure overcomes membrane resistance.This happens due to weakening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Some obstetricians recommend immediate intervention, 2,9 while others argue there is no difference in result. 5,10,11 Our study was carried out on near-term and term PROM patients because neonates of this gestation rarely suffer from prematurity-related complications; thus, the morbidity arising from rupture of membranes may be studied more easily. It is clear from our results that, as the duration from rupture of membranes to delivery increases, so does the risk of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some obstetricians recommend immediate intervention, 2,9 while others argue there is no difference in result. 5,10,11 Our study was carried out on near-term and term PROM patients because neonates of this gestation rarely suffer from prematurity-related complications; thus, the morbidity arising from rupture of membranes may be studied more easily. It is clear from our results that, as the duration from rupture of membranes to delivery increases, so does the risk of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Some obstetricians recommend immediate intervention, 2,9 while others argue there is no difference in result. 5,10,11…”
Section: Discussionmentioning
confidence: 99%
“…Mode of birth was reported in seven studies, although Yasmin et al (2013) only reported on caesarean births, and Poornima and Dharma Reddy (2011) claimed results but did not provide figures. Vaginal birth was more frequent for women with induced labour versus expectant management in four studies (Ayaz et al, 2008;Hannah et al, 1996;Rawat et al, 2018;Sadeh-Mestechkin et al, 2016), and more frequent for women with expectant management in three studies (Agnes & Lavanya, 2018;Ashwal et al, 2016;Shah & Doshi, 2012). Instrumental births were reported by four studies and also showed conflicting results with no significant p values (Agnes & Lavanya, 2018;Poornima & Dharma Reddy, 2011;Rawat et al, 2018;Sadeh-Mestechkin et al, 2016).…”
Section: Management Of Prommentioning
confidence: 99%
“…Vaginal birth was more frequent for women with induced labour versus expectant management in four studies (Ayaz et al, 2008;Hannah et al, 1996;Rawat et al, 2018;Sadeh-Mestechkin et al, 2016), and more frequent for women with expectant management in three studies (Agnes & Lavanya, 2018;Ashwal et al, 2016;Shah & Doshi, 2012). Instrumental births were reported by four studies and also showed conflicting results with no significant p values (Agnes & Lavanya, 2018;Poornima & Dharma Reddy, 2011;Rawat et al, 2018;Sadeh-Mestechkin et al, 2016). Similarly, caesarean births were also reported with enough variation in results that no conclusion could be drawn.…”
Section: Management Of Prommentioning
confidence: 99%
See 1 more Smart Citation